Well logging evaluation of clastic reservoir productivity in the Wulanhua depression, Hailaer basin, China - Huang, Xianhua; Fan, Houjiang; Tang, Jianru; Zhao, Jialin; Li, Jin (Frontiers in Earth Science, 2026)
Productivity evaluations are essential for reservoir characterization and development, particularly in low-porosity and low-permeability clastic systems. In the Wulanhua (WH) depression of the Hailaer basin in China, most reservoirs exhibit porosities below 15% and permeabilities lower than 100 × 10−3 μm2, posing significant challenges for reliable productivity prediction. To address this, a multisource tiered evaluation approach is proposed herein that integrates mercury injection capillary pressure, nuclear magnetic resonance (NMR), and conventional well logging data. Quantitative analysis shows that reservoirs with mean pore-throat radii greater than 0.12 μm and displacement pressures below 5 MPa generally achieve natural productivities above 20 t/d, whereas those with radii below 0.05 μm require stimulation to reach industrial levels. NMR-based parameters, including an S2 + S3 pore fraction exceeding 65% and a T2 geometric mean time greater than 20 ms, correspond to high-yield zones (>15 t/d). When only conventional logs are available, deep resistivity (>20 Ω·m), low natural gamma (<70 API), and a resistivity multiplication coefficient (AII) exceeding 1 × 106 can effectively be used to discriminate productive intervals. Field validation of this approach demonstrates that the integrated scheme predicts the well productivity with an average deviation of ±15%. The novelty of this study lies in the establishment of a quantitative and multitiered evaluation framework that is adaptable to varying data availability, providing a robust reference for efficient development of tight clastic reservoirs in the WH depression and similar basins.